An assessment of schoolyard renovation strategies to encourage children's physical activity - Greenwood Emily; Lampe Sarah; Brink Lois; Anthamatten Peter; Kingston Beverly; Nigg Claudio (BMC, 2011)
Abstract Background Children in poor and minority neighborhoods often lack adequate environmental support for healthy physical development and community interventions designed to improve physical activity resources serve as an important approach to addressing obesity. In Denver, the Learning Landscapes (LL) program has constructed over 98 culturally-tailored schoolyard play spaces at elementary schools with the goal to encourage utilization of play spaces and physical activity. In spite of enthusiasm about such projects to improve urban environments, little work has evaluated their impact or success in achieving their stated objectives. This study evaluates the impacts of LL construction and recency of renovation on schoolyard utilization and the physical activity rates of children, both during and outside of school, using an observational study design. Methods This study employs a quantitative method for evaluating levels of physical activity of individuals and associated environmental characteristics in play and leisure environments. Schools were selected on the basis of their participation in the LL program, the recency of schoolyard renovation, the size of the school, and the social and demographic characteristics of the school population. Activity in the schoolyards was measured using the System for Observing Play and Leisure Activity (SOPLAY), a validated quantitative method for evaluating levels of physical activity of individuals in play and leisure environments. Trained observers collected measurements before school, during school recess, after school, and on weekends. Overall utilization (the total number of children observed on the grounds) and the rate of activity (the percentage of children observed who were physically active) were analyzed. Observations were compared using t-tests and the data were stratified by gender for further analysis. In order to assess the impacts of LL renovation, recently-constructed LL schoolyards were compared to LL schoolyards with older construction, as well as un-renovated schoolyards. Results Overall utilization was significantly higher at LL schools than at un-renovated schools for most observation periods. Notably, LL renovation had no impact on girl's utilization on the weekends, although differences were observed for all other periods. There were no differences in rates of activity for any comparison. With the exception of the number of boys observed, there was no statistically significant difference in activity when recently-constructed LL schools are compared to LL schools with older construction dates and there was no difference observed in comparisons of older LL with unrenovated sites. Conclusions While we observed greater utilization and physical activity in schools with LL, the impact of specific features of LL renovation is not clear. However, schoolyard renovation and programs to encourage schoolyard use before and after school may offer a means to encourage greater physical activity among children, and girls in particular. Additional study of schoolyard renovation may shed light on the specific reasons for these findings or suggest effective policies to improve the physical activity resources of poor and minority neighborhoods.